Materialists [videorecording (Blu-Ray)] - Pemberton, Daniel (A24, 2025)
"Lucy is a young, ambitious New York City matchmaker who thinks she has love down to a formula. But when she meets a tall, dark, and handsome 'unicorn' on the same night as a chance encounter with a broke old boyfriend, she's suddenly torn between the perfect match and her imperfect ex."--